2014
DOI: 10.5812/jjm.11370
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Various Plants Extracts Against Antibiotic-resistantAeromonas hydrophila

Abstract: Background:Aeromonas hydrophila cause one of the most important diseases in fishes and lead to economic losses, and may be contaminated human beings.Objectives:The current research aimed to investigate the anti-bacterial activity shown by the extracts prepared from different parts of Olea europea, Myrtus communis, Thymus vulgaris, Rosmarinuis officinalis, and Achillea falcata that grow in Syria against A. hydrophila that causes the most dangerous bacterial diseases in fish.Materials and Methods:The study was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…The qualitative UV-VIS spectrum profile of the chloroform extract of C. asiatica at a wavelength from 400 to 900 nm showed peaks at 677, 542 and 443 nm with the absorption of 0.318, 0.303 and 0.301 respectively, which can serve as a baseline for future characterization of the extract. Considerable research has been carried out on the phytochemical properties of the plants, which have been amply reviewed [4,9,20,22]. It has been reported that the plant extracts consisted of triterpenoid glycosides, free acids, volatile oils and flavonoids [11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The qualitative UV-VIS spectrum profile of the chloroform extract of C. asiatica at a wavelength from 400 to 900 nm showed peaks at 677, 542 and 443 nm with the absorption of 0.318, 0.303 and 0.301 respectively, which can serve as a baseline for future characterization of the extract. Considerable research has been carried out on the phytochemical properties of the plants, which have been amply reviewed [4,9,20,22]. It has been reported that the plant extracts consisted of triterpenoid glycosides, free acids, volatile oils and flavonoids [11].…”
Section: Resultsmentioning
confidence: 99%
“…However, considering the inherent negative effects of antibiotics, other alternative antimicrobials from plant origins are increasingly used in aquaculture [3]. Since prehistoric times, herbs were the basis for nearly all medicinal therapy until synthetic drugs were developed in the 19 th century [4]. Medicinal plants have many traditionally reported properties including the treatment of ailments of infectious origin.…”
Section: Introductionmentioning
confidence: 99%
“…Herbs with potential antibacterial activity against Aeromonas hydrophila have a crucial role in disease management in aquaculture [13]. Extracts from herbs, such as Acorus calamus , Indigofera aspalathoides , Coleus aromaticus , Thymus vulgaris , and Trifolium pannonicum , have been reported to effectively inhibit pathogenic A. hydrophila [14,15,16,17]. Many studies have also proved that oral administration of extracts from herbs, such as Allium sativum , Epilobium hirsutum , Panax quinquefolium , and Toona sinensis , can greatly enhance resistance against A. hydrophila infection in fish [18,19,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Many herbal medicines have been found to be effective against fish pathogens (Birinci Y2ld2r2m and 2018). Some studies report on the antimicrobial activities of essential oils on aquatic animal diseases (Al Laham et al 2014). Treatments with medicinal plants that have antibacterial properties is a potentially beneficial alternative in aquaculture (Madhuri et al 2012, Turker andY2ld2r2m 2015, Birinci 16 Halyna Tkachenko et al Y2ld2r2m and Turker 2018).…”
Section: Introductionmentioning
confidence: 99%